Hydrogen sulfide signaling in plant response to temperature stress - Li, Zhong-Guang; Fang, Jue-Rui; Bai, Su-Jie (Frontiers in Plant Science, 2024)
For the past 300 years, hydrogen sulfide (H2S) has been considered a toxic gas. Nowadays, it has been found to be a novel signaling molecule in plants involved in the regulation of cellular metabolism, seed germination, plant growth, development, and response to environmental stresses, including high temperature (HT) and low temperature (LT). As a signaling molecule, H2S can be actively synthesized and degraded in the cytosol, chloroplasts, and mitochondria of plant cells by enzymatic and non-enzymatic pathways to maintain homeostasis. To date, plant receptors for H2S have not been found. It usually exerts physiological functions through the persulfidation of target proteins. In the past 10 years, H2S signaling in plants has gained much attention. Therefore, in this review, based on that same attention, H2S homeostasis, protein persulfidation, and the signaling role of H2S in plant response to HT and LT stress were summarized. Also, the common mechanisms of H2S-induced HT and LT tolerance in plants were updated. These mechanisms involve restoration of biomembrane integrity, synthesis of stress proteins, enhancement of the antioxidant system and methylglyoxal (MG) detoxification system, improvement of the water homeostasis system, and reestablishment of Ca2+ homeostasis and acid-base balance. These updates lay the foundation for further understanding the physiological functions of H2S and acquiring temperature-stress-resistant crops to develop sustainable food and agriculture.